Pengaruh E-Commerce Terhadap Perilaku Konsumtif Masyarakat Di Kelurahan Karang Panjang Kota Ambon - Zuhria Nurul 'Ainy (Universitas Hamzanwadi, 2020)
The development of technology and ease of information is currently very influencing in all aspects of life, for example, the use of social media is not only used as a means of obtaining information and as a means of self-presentation, but social media is widely used as a means of doing business which we usually call an online shop. With technology that is increasingly developing, nowadays there are many online buying and selling sites wherein it collects many online shops into one site that makes it easier for buyers to get the items they want with various promos that attract people to shop on these sites. The purpose of this study is to determine whether e-commerce has an effect on people's consumptive behavior. The data collection technique used was a questionnaire, while the method used in this study was a descriptive quantitative method with a sample of 117 people who work as housewives and mothers who work by distributing questionnaires. The results showed that there is an effect of e-commerce on the consumer's behavior in Karang Panjang Village, Ambon City, this is shown by the correlation test data that has been carried out, the regression line equation Y = Î± + Î²X is Y = 16.890 + 0.491X and the regression results are obtained. r count = 0.762 and the significance level is 5% with N = 117